Slurry for forming positive electrode active material layer of lithium ion battery and manufacturing method thereof, positive electrode of lithium ion battery, and lithium ion battery
The slurry for lithium-ion batteries, incorporating modified graphene with an organic acid and lithium ions, addresses the aggregation issues in existing technologies, resulting in improved discharge rate characteristics by ensuring effective dispersion and conductivity in the positive electrode active material layer.
Patent Information
- Application Number
- JP2023145517
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-07
- Publication Date
- 2025-03-19
AI Technical Summary
Existing lithium-ion batteries face challenges in achieving excellent discharge rate characteristics due to the aggregation of graphene and carbon nanotubes, which affects the formation of sufficient conductivity paths in the positive electrode active material layer.
A slurry for forming a positive electrode active material layer is developed, comprising a positive electrode active material, a binder, a diluent solvent, and a conductive aid containing modified graphene. The modified graphene has an anionic portion bound to an organic acid and lithium ions, improving dispersibility and reducing the need for conventional dispersants.
The slurry enables the manufacture of lithium-ion batteries with enhanced discharge rate characteristics by ensuring homogeneous dispersion of modified graphene, thereby reducing agglomeration and improving conductivity.
Smart Images

Figure 2025038731000001 
Figure 2025038731000002 
Figure 2025038731000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a slurry for forming a positive electrode active material layer of a lithium ion battery and a method for producing the same. The present invention also relates to a positive electrode of a lithium ion battery and a lithium ion battery including the positive electrode. [Background technology]
[0002] The materials forming the positive electrode active material layer of a lithium-ion battery are essentially composed of a positive electrode active material, a binder, and a conductive additive. The conductive additive is a material used to reduce the resistance of the electrode and improve the conductivity. Currently, carbon black is the mainstream conductive additive, but the use of other carbon materials such as graphene and carbon nanotubes is also being considered. Graphene and carbon nanotubes, which are nanomaterials, tend to aggregate easily, and various methods for controlling dispersibility are being considered.
[0003] In order to disperse graphene or carbon nanotubes, it is common to add a small amount of a so-called dispersant or surfactant (for example, Patent Documents 1 and 2, Non-Patent Document 1). It is not easy to determine the type, model, and amount of the dispersant, etc., and this is the most important know-how of the manufacturer.
[0004] Patent Document 3 discloses a method for producing an inorganic particle composite, which includes a step (A) of adding a water-soluble salt to an inorganic powder and mixing the powder in a dry or paste form, and a step (B) of washing with water after the step (A) to obtain an inorganic particle composite containing a component derived from the water-soluble salt, wherein the water-soluble salt is a water-soluble salt having an acid dissociation constant pKa(H2O) of a counter anion of the water-soluble salt that is greater than 0. Patent Document 3 describes graphene as one example of the inorganic particle composite. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2022-167301 A [Patent Document 2] International Publication No. 2022 / 075387 [Patent Document 3] JP 2019-147713 A [Non-patent literature]
[0006] [Non-Patent Document 1] Synthesis and Dispersion of Carbon Nanotubes and Their Applications, Journal of the Adhesion Society of Japan, Japan Adhesion Society, 2019, Vol. 1.55, No. 1, p35-41 Summary of the Invention [Problem to be solved by the invention]
[0007] In terms of performance, it is desirable not to add substances such as dispersants that are not necessary for the performance of the battery to the final product, the lithium ion battery, but in reality, they are inevitably added due to the above-mentioned dispersibility problem.
[0008] In the aggregated state, graphene does not form a sufficient conductive path when a positive electrode active material layer is formed, so in general, when graphene is used as a conductive assistant, the graphene is mixed with other materials in the form of a dispersion liquid. In order to improve battery performance such as discharge rate characteristics, it is considered important to increase the dispersibility with components that have little effect on battery performance. In Patent Document 3, the dispersibility of various inorganic particle composites is examined, but the use as a material for lithium ion batteries is not examined, and there is room for improvement in using them as a material for lithium ion batteries.
[0009] Under such circumstances, an object of the present invention is to provide a slurry for forming a positive electrode active material layer of a lithium ion battery, which can produce a lithium ion battery having excellent discharge rate characteristics, and a method for producing the same. Another object of the present invention is to provide a positive electrode using the slurry, and a lithium ion battery using the positive electrode. That is, the present invention relates to the following inventions. [Means for solving the problem]
[0010] As a result of intensive research aimed at solving the above problems, the present inventors found that the following invention meets the above object, and thus completed the present invention.
[0011] <1> A slurry for forming a positive electrode active material layer of a lithium ion battery, comprising: a positive electrode active material, a binder, a dilution solvent, and a conductive assistant containing modified graphene, wherein the modified graphene contains graphene having an anionic site to which an organic acid is bonded, and lithium ions. <2> the slurry contains the positive electrode active material, the binder, the dilution solvent, and a graphene dispersion, the graphene dispersion being a dispersion containing the modified graphene, a graphene-dispersibility-improving polymer that constitutes at least a part of the binder, and a graphene dispersion solvent that constitutes at least a part of the dilution solvent; <1> 2. A slurry for forming a positive electrode active material layer of a lithium ion battery according to claim 1. <3> The binder is a fluorine-based polymer, and the dilution solvent is N-methyl-2-pyrrolidone. <1> or <2> 2. A slurry for forming a positive electrode active material layer of a lithium ion battery according to claim 1. <4> The organic acid is citric acid. <1> from <3> 2. A slurry for forming a positive electrode active material layer of a lithium ion battery according to claim 1 . <5> The graphene dispersion improving polymer has a weight average molecular weight (Mw) of 600,000 or more. <2> 2. A slurry for forming a positive electrode active material layer of a lithium ion battery according to claim 1. <6> The conductive assistant contains the modified graphene and carbon black and / or carbon nanotubes. <1> from <5> 2. A slurry for forming a positive electrode active material layer of a lithium ion battery according to claim 1 .
[0012] <7> The method includes at least a step of mixing the positive electrode active material, the binder, the dilution solvent, and a graphene dispersion to obtain a slurry, and the graphene dispersion is a dispersion in which the modified graphene is dispersed in a graphene dispersion solvent that is at least a part of the dilution solvent. <1> 5> A method for producing a slurry for forming a positive electrode active material layer of a lithium ion battery according to any one of the above items 1 to 5>. <8> the graphene dispersion includes the modified graphene, a graphene-dispersibility-improving polymer that constitutes at least a part of the binder, and the graphene dispersion solvent, and, prior to the step of obtaining the slurry, includes a step (A) of grinding, while mixing in a dry state or in a paste state, an organic acid lithium salt that is a salt of an organic acid and lithium ions, and graphite, a step (B) of washing the mixture obtained in the step (A) with water to obtain a graphite composite of the graphite and the organic acid lithium salt, and a step (C) of mixing, while applying a shear force, the graphite composite and a dispersion solution in which the graphene-dispersibility-improving polymer is dissolved in the graphene dispersion solvent, to exfoliate the graphite composite in the dispersion solution, thereby obtaining the graphene dispersion, wherein the viscosity of the dispersion solution in the step (C) is 3.0 mPa s to 25.0 mPa s and the surface tension of the dispersion solution is 10 mN / m to 60 mN / m. <7> A method for producing a slurry for forming a positive electrode active material layer of a lithium ion battery according to claim 1. <9> the slurry contains the modified graphene, and carbon black and / or carbon nanotubes as the conductive assistant, and in the step of obtaining the slurry, the positive electrode active material, the binder, the dilution solvent, the graphene dispersion, and a powder or a dispersion of the carbon black and / or the carbon nanotubes are mixed to obtain a slurry; <7> or <8> A method for producing a slurry for forming a positive electrode active material layer of a lithium ion battery according to claim 1.
[0013] <10> A positive electrode of a lithium ion battery comprising: a current collector; and a positive electrode active material layer formed on the current collector, the positive electrode active material layer including a positive electrode active material, a binder, and a conductive assistant including modified graphene, the modified graphene including graphene having an anionic site to which an organic acid is bonded, and lithium ions. <11> The above <10> A lithium ion battery comprising the positive electrode according to claim 1. Effect of the Invention
[0014] According to the present invention, there are provided a slurry for forming a positive electrode active material layer of a lithium ion battery, which can produce a lithium ion battery having excellent discharge rate characteristics, and a method for producing the same. Also provided are a positive electrode using the slurry, and a lithium ion battery using the positive electrode. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The following is a detailed description of the embodiments of the present invention, but the following description of the constituent elements is one example (representative example) of the embodiment of the present invention, and the present invention is not limited to the following content as long as the gist of the present invention is not changed. Note that in this specification, when the expression "~" is used, it is used as an expression including the numerical value or physical property value before and after it.
[0016] <Slurry for forming positive electrode active material layer of lithium ion battery> The present invention relates to a slurry for forming a positive electrode active material layer of a lithium ion battery (hereinafter, may be simply referred to as "slurry" or "slurry of the present invention") which includes a positive electrode active material, a binder, a dilution solvent, and a conductive assistant containing modified graphene, where the modified graphene includes graphene having an anionic site to which an organic acid is bonded, and lithium ions.
[0017] The modified graphene contained in the slurry of the present invention has an anionic site to which an organic acid is bonded, which induces electrostatic repulsion between graphene layers and improves dispersibility, and the slurry can have excellent dispersibility even without adding a dispersant as in the past. By configuring the slurry of the present invention, the modified graphene is less likely to aggregate or settle, and each component can be uniformly dispersed. By using the slurry in the manufacture of a lithium ion battery, a lithium ion battery with excellent discharge rate characteristics can be manufactured.
[0018] (Cathode active material) The positive electrode active material is not particularly limited, but examples thereof include oxides such as LiMn2O4, LiCoO2, and LiNiO2, olivines such as LiFePO4, and Li(Ni 1 / 3 Mn 1 / 3 Co 1 / 3 )O2 and other ternary systems. These may be used alone or in combination of two or more.
[0019] (binder) The binder is not particularly limited, and examples thereof include fluorine-based polymers such as polyvinylidene fluoride and polytetrafluoroethylene; polyimide, etc. These may be used alone or in combination of two or more. The binder is preferably a fluorine-based polymer, and more preferably polyvinylidene fluoride. Polyvinylidene fluoride may be a homopolymer or a copolymer of vinylidene fluoride. The amount of the binder may be, for example, 1 to 10 parts by mass, or 3 to 8 parts by mass, relative to 100 parts by mass of the positive electrode active material.
[0020] (Dilution Solvent) The dilution solvent is used to adjust the solid content concentration of the slurry. Examples of the dilution solvent include N-methyl-2-pyrrolidone (NMP), N-ethyl-2-pyrrolidone (NEP), N,N-dimethylformamide, N,N-dimethylacetamide, N,N-diethylacetamide, N-methylcaprolactam, methanol, ethanol, n-propanol, 2-propanol, butanol, n-butanol, sec-butanol, tert-butanol, benzyl alcohol, acetone, tetrahydrofuran, methyl ethyl ketone, acetonitrile, and dimethyl sulfoxide, and N-methyl-2-pyrrolidone (NMP) is more preferable. The solid content concentration of the slurry is appropriately set in consideration of the coating method and coatability, and is adjusted to the target solid content concentration of the slurry using the dilution solvent. The solid content concentration of the slurry can be, for example, 40% by mass to 80% by mass, or 50 parts by mass to 70 parts by mass.
[0021] (Conductive assistant) The conductive assistant essentially contains modified graphene, but may contain a carbon material other than modified graphene. That is, the conductive assistant may be made of modified graphene, or may be made of modified graphene and a carbon material other than modified graphene. The conductive assistant may be, for example, 0.5 to 10 parts by mass, 1 to 8 parts by mass, or 2 to 6 parts by mass relative to 100 parts by mass of the positive electrode active material.
[0022] (Modified graphene) The modified graphene contains graphene having an anionic site to which an organic acid is bonded and lithium ions, and functions as a conductive assistant. In the modified graphene, an organic acid is bonded to the carbon atom on the surface of the graphene, and the organic acid forms a negatively charged anionic site, and it is considered that the lithium ion exists in the vicinity of the anionic site. By using such modified graphene, not only is the dispersibility excellent, but the lithium ion existing as a counter cation of the anionic site is contained in the lithium ion battery, and the effect on the battery performance is small. The bond may be any of a covalent bond, an ionic bond, and a coordinate bond. The graphene having an anionic site is a multilayer or single layer, and the average particle size is preferably 1000 nm or less. Examples of the organic acid forming the anionic site of the graphene include citric acid, glutamic acid, acetic acid, and tartaric acid, and the organic acid bonded to the graphene may be in the form of an ion.
[0023] Among them, the modified graphene preferably contains graphene having an anionic site to which citric acid is bound and lithium ions.
[0024] (Other carbon materials) The conductive assistant may contain a carbon material other than the modified graphene. Examples of the carbon material other than the modified graphene include carbon black such as acetylene black and Ketjen Black (registered trademark); carbon nanotubes; and graphene other than the modified graphene. In this case, the slurry contains a positive electrode active material, a binder, a dilution solvent, and a conductive assistant made of the modified graphene and the other carbon material. The ratio of the modified graphene:other carbon material (w / w) can be 100-1:0-99, 75-2:25-98, or 50-3:50-97.
[0025] For example, the conductive aid may include modified graphene, carbon black and / or carbon nanotubes.
[0026] As described later, the slurry of the present invention preferably contains a positive electrode active material, a binder, a dilution solvent, and a graphene dispersion, and the graphene dispersion preferably contains modified graphene, a graphene-dispersibility-improving polymer that constitutes at least a part of the binder, and a graphene dispersion solvent that constitutes at least a part of the dilution solvent.
[0027] The slurry of the present invention is preferably a slurry containing a positive electrode active material, a conductive assistant containing modified graphene, a fluorine-based polymer, and N-methyl-2-pyrrolidone. That is, it is preferable that the binder, or the binder and the graphene dispersion improving polymer, are fluorine-based polymers, and the dilution solvent, or the dilution solvent and the graphene dispersion solvent, are N-methyl-2-pyrrolidone. In addition, when the binder and the graphene dispersion improving polymer are fluorine-based polymers, the fluorine-based polymer used as the binder and the fluorine-based polymer used as the graphene dispersion improving polymer may have the same molecular weight or bonding mode or may be different. For example, they may have different molecular weights, or one may be a homopolymer of polyvinylidene fluoride and the other may be a copolymer thereof.
[0028] In the case of a slurry containing a positive electrode active material, a conductive assistant containing modified graphene, a fluorine-based polymer, and N-methyl-2-pyrrolidone, the total content of the positive electrode active material, the conductive assistant containing modified graphene, the fluorine-based polymer, and N-methyl-2-pyrrolidone in the slurry is preferably 90% by mass or more, more preferably 95% by mass or more, and even more preferably 99% by mass or more. The slurry is preferably substantially composed of a positive electrode active material, a conductive assistant containing modified graphene, a fluorine-based polymer, and N-methyl-2-pyrrolidone, or substantially composed of a positive electrode active material, a modified graphene, carbon black and / or carbon nanotubes, a fluorine-based polymer, and N-methyl-2-pyrrolidone. That is, the slurry preferably does not contain any components other than the positive electrode active material, the conductive assistant containing modified graphene, the fluorine-based polymer, and N-methyl-2-pyrrolidone, except for unavoidable impurities.
[0029] [Method of manufacturing slurry] The slurry of the present invention can be suitably produced by a method for producing a slurry for forming a positive electrode active material layer of a lithium ion battery (hereinafter, may be referred to as "the method for producing the slurry of the present invention"), which includes at least a step of mixing a positive electrode active material, a binder, a dilution solvent, and a graphene dispersion to obtain a slurry, and the graphene dispersion is a dispersion in which modified graphene is dispersed in a graphene dispersion solvent. More preferably, the graphene dispersion is produced by using a dispersion containing modified graphene, a graphene dispersion improving polymer, and a graphene dispersion solvent.
[0030] The positive electrode active material, binder and dilution solvent used in the preparation of the slurry are as described above.
[0031] (Graphene dispersion) The graphene dispersion is a dispersion in which modified graphene is dispersed in a graphene dispersion solvent. As described above, the modified graphene contains an anionic site, which induces electrostatic repulsion between graphene layers, and has excellent dispersibility in the dispersion without adding a dispersant as in the past. However, in order to further increase the dispersibility and dispersion stability, the graphene dispersion preferably further contains a graphene dispersion improving polymer that also functions as a binder. In this way, by using a graphene dispersion improving polymer that functions as a binder to improve the dispersibility of the modified graphene, the graphene dispersion does not contain a dispersant such as a surfactant that is unnecessary for battery performance, so that it is only necessary to reduce the amount of the binder when preparing the slurry, and there is almost no problem in the electrode performance.
[0032] (Graphene dispersion improving polymer) The graphene dispersion improving polymer is a component that functions as a binder and improves the dispersibility of graphene. The graphene dispersion improving polymer may be one that can be dissolved in the graphene dispersion solvent to adjust the graphene dispersion to a predetermined viscosity and surface tension, and can function as a binder in the slurry, and one similar to the binder described above can be appropriately selected and used according to the type of dispersion solvent. One type of graphene dispersion improving polymer may be used, or two or more types may be used in combination. Among them, it is preferable that the graphene dispersion improving polymer has polarity. It is considered that the use of a polar polymer can enhance the effect of peeling off graphene due to electrostatic repulsion during the preparation of the graphene dispersion described later. The graphene dispersion improving polymer may be the same as or different from the binder, but it is preferable to use the same type.
[0033] Specifically, the graphene dispersion improving polymer is preferably a fluorine-based polymer, more preferably polyvinylidene fluoride. Polyvinylidene fluoride may be a homopolymer of vinylidene fluoride or a copolymer of vinylidene fluoride and another monomer.
[0034] The graphene dispersion improving polymer preferably has a weight average molecular weight (Mw) of 600,000 or more, more preferably 600,000 to 1,500,000, and even more preferably 800,000 to 1,200,000. Use of such a high molecular weight polymer is preferable because it is easy to adjust the viscosity and surface tension of the dispersion solution used for preparing the graphene dispersion to a suitable range described later while reducing the amount of the graphene dispersion improving polymer in the dispersion solution described later. The weight average molecular weight (Mw) can be determined by gel permeation chromatography (GPC).
[0035] (Graphene dispersion solvent) The graphene dispersion solvent is a component that is at least a part of the dilution solvent contained in the slurry. A polar solvent can be used as the graphene dispersion solvent. The graphene dispersion solvent can be appropriately selected depending on the type of graphene dispersion improving polymer, and examples thereof include N-methyl-2-pyrrolidone (NMP), N-ethyl-2-pyrrolidone (NEP), N,N-dimethylformamide, N,N-dimethylacetamide, N,N-diethylacetamide, N-methylcaprolactam, water, acetone, ethanol, methanol, 2-propanol, butanol, n-butanol, sec-butanol, tert-butanol, benzyl alcohol, tetrahydrofuran, methyl ethyl ketone, acetonitrile, dimethylformamide, and dimethyl sulfoxide. These may be used alone or in combination of two or more. The graphene dispersion solvent may be the same as or different from the dilution solvent, but is preferably the same. When a fluoropolymer is used as the graphene dispersion improving polymer, it is preferable to use N-methyl-2-pyrrolidone as the graphene dispersion solvent.
[0036] From the viewpoint of dispersibility, the graphene dispersion preferably has a modified graphene content of 0.05% to 8% by mass, a graphene dispersion improving polymer content of 0% to 2% by mass, and a graphene dispersion solvent content of 90% to 99.95% by mass, more preferably has a modified graphene content of 0.5% to 6% by mass, a graphene dispersion improving polymer content of 0.2% to 1.5% by mass, and a graphene dispersion solvent content of 92.5% to 98.5% by mass, and further preferably has a modified graphene content of 1.5% to 5% by mass, a graphene dispersion improving polymer content of 0.3 to 1% by mass, and a graphene dispersion solvent content of 94% to 98% by mass. In addition, when the graphene dispersion improving polymer is included, the graphene dispersion improving polymer may be 0.01 parts by mass to 1 part by mass, 0.02 parts by mass to 0.5 parts by mass, etc., relative to 1 part by mass of the modified graphene.
[0037] The graphene dispersion preferably contains modified graphene, a fluorine-based polymer, and a graphene dispersion solvent. As described above, in the past, in order to ensure the dispersibility of graphene for a long period of time, it was common to add a dispersant such as a surfactant or polyvinylpyrrolidone to prepare the graphene dispersion. On the other hand, regardless of the possibility of affecting the battery performance, it is desired to increase the positive electrode active material by even 1% by adding as few components as possible other than the essential components. Since the fluorine-based polymer also functions as a binder, it is preferable that a graphene dispersion that can maintain the dispersibility of modified graphene well for a long period of time without any problems in terms of battery performance can be obtained without using a dispersant such as a surfactant or polyvinylpyrrolidone.
[0038] Furthermore, the graphene dispersion preferably contains modified graphene, a fluorine-based polymer, and N-methyl-2-pyrrolidone, more preferably contains modified graphene, polyvinylidene fluoride, and N-methyl-2-pyrrolidone, and further preferably contains graphene having an anionic site to which citric acid is bound, modified graphene containing lithium ions, polyvinylidene fluoride, and N-methyl-2-pyrrolidone.
[0039] The graphene dispersion used for producing the slurry preferably contains modified graphene, a graphene dispersibility improving polymer, and a graphene dispersion solvent as main components, and the total content of the modified graphene, the graphene dispersibility improving polymer, and the graphene dispersion solvent in the graphene dispersion can be 80 mass% or more, 90 mass% or more, 95 mass% or more, 98 mass% or more, 99 mass% or more, etc. In addition, the graphene dispersion can be one that does not contain a conventional dispersant such as a surfactant or polyvinylpyrrolidone, and is preferably one that is substantially composed of the modified graphene, the graphene dispersibility improving polymer, and the graphene dispersion solvent. In other words, the graphene dispersion preferably does not contain any components other than the modified graphene, the graphene dispersibility improving polymer, and the graphene dispersion solvent, except for unavoidable impurities.
[0040] (Preparation of graphene dispersion) The graphene dispersion used in the present invention is preferably one obtained by a method including: step (A) of grinding an organic acid lithium salt, which is a salt of an organic acid and lithium ions, and graphite while mixing them in a dry or paste state, step (B) of washing the mixture obtained in step (A) with water to obtain a graphite composite of the graphite and the organic acid lithium salt, and step (C) of mixing the graphite composite and a dispersion solution in which a graphene dispersibility improving polymer is dissolved in a graphene dispersion solvent while applying a shear force, and exfoliating the graphite composite in the dispersion solution to obtain a graphene dispersion. The method for producing a slurry of the present invention may include steps (A) to (C) before the step of obtaining a slurry.
[0041] In the graphite composite of graphite and organic acid lithium salt obtained in step (B), an organic acid component derived from the organic acid lithium salt is bonded to graphite, and lithium ions are present in the vicinity of anionic sites of graphite to which the organic acid is bonded. In step (C), the graphite composite is delaminated to obtain a graphene dispersion that contains modified graphene, a graphene dispersion improving polymer, and a graphene dispersion solvent. The graphene dispersion obtained by such a method is a dispersion with excellent dispersibility of modified graphene, and therefore the modified graphene can be well dispersed even in a slurry produced using the graphene dispersion. By utilizing the slurry in the production of a lithium ion battery, a lithium ion battery with excellent discharge rate characteristics can be produced.
[0042] (Process (A)) In step (A), graphite and an organic acid lithium salt are mixed in a dry state or in a paste state and pulverized, whereby the graphite reacts with a part of the organic acid lithium salt to produce a graphite composite of the graphite and the organic acid lithium salt.
[0043] (graphite) The type of graphite is not particularly limited, and any of flake graphite, lump graphite, swollen graphite, amorphous graphite, artificial graphite, etc. is usable. From the viewpoint of facilitating the preparation of a dispersion in which thinner graphene is dispersed, flake graphite is preferably used.
[0044] (Lithium salts of organic acids) The organic acid lithium salt is a compound of an organic acid and a lithium ion. Specific examples include lithium citrate, lithium glutamate, lithium acetate, and lithium tartrate.
[0045] The graphite and the lithium salt of an organic acid are mixed and pulverized in a dry state or in a paste state. Mixing in a paste state means mixing in a state where the viscosity is high but fluidity is recognized. Specifically, the viscosity of the mixture is 1 / 100 at 20°C and a shear rate of 1 s -1 This means that the mixture is mixed at a viscosity of about 0.01 to 500 Pa·s.
[0046] The method of mixing and pulverization is not particularly limited, and known methods can be used, for example, a bead mill, a jet mill, a hammer mill, a high-speed stirrer, etc. The time for mixing and pulverization is not particularly limited, and can be, for example, about 10 minutes to 3 hours, or about 15 minutes to 2 hours.
[0047] The mixing ratio of graphite to the organic acid lithium salt can be, for example, 0.01 to 100 parts by mass, 0.1 to 10 parts by mass, or 0.5 to 5 parts by mass of the organic acid lithium salt per 1 part by mass of graphite.
[0048] (Process (B)) Step (B) is a step of washing the mixture obtained in step (A) with water to obtain a graphite composite of graphite and an organic acid lithium salt. The mixture obtained in step (A) contains unreacted organic acid lithium salt in addition to the graphite composite produced by the reaction of graphite with the organic acid lithium salt. The mixture obtained in step (A) is washed with water to remove the unreacted organic acid lithium salt, thereby recovering a graphite composite of graphite and an organic acid lithium salt (sometimes simply referred to as "graphite composite"). The lithium ion concentration of the obtained graphite composite is about 1 to 100,000 ppm, or about 35 to 10,000 ppm.
[0049] The mixture obtained in step (A) can be washed with water by mixing the mixture obtained in step (A) with water for a predetermined time, and then filtering to remove the water. The washing with water may be performed multiple times. There is no particular limit to the amount of water used, but it is preferable to add an excess amount of water to the mixture, such as 50 parts by mass or more, 100 parts by mass or more, or 200 parts by mass or more per part by mass of the mixture, each time.
[0050] (Process (C)) Step (C) is a step of mixing the graphite composite obtained in step (B) with a dispersion solution in which a graphene-dispersibility improving polymer is dissolved in a graphene dispersion solvent while applying a shear force, thereby exfoliating the graphite composite in the dispersion solution to obtain a graphene dispersion.
[0051] (Dispersion solution) The dispersion solution used in step (C) is a solution in which a graphene dispersion improving polymer is dissolved in a graphene dispersion solvent. If the ratio of the graphene dispersion improving polymer in the dispersion solution is too high, the performance of the lithium ion battery to be manufactured may be affected. Therefore, in the dispersion solution, the mass ratio of the graphene dispersion improving polymer to the graphene dispersion solvent (mass of graphene dispersion improving polymer / mass of graphene dispersion solvent×100(%)) is preferably 0.2% by mass to 1% by mass, more preferably 0.3% by mass to 0.8% by mass.
[0052] The graphene dispersibility improving polymer and graphene dispersion solvent contained in the dispersion solution are as described above. When a fluorine-based polymer is used as the graphene dispersibility improving polymer, it is preferable to use N-methyl-2-pyrrolidone as the graphene dispersion solvent.
[0053] (viscosity) The viscosity of the dispersion solution is preferably 3.0 mPa·s to 25.0 mPa·s. By setting the viscosity of the dispersion solution to 3.0 mPa·s or more, the graphite composite is easily delaminated, and the dispersibility and dispersion stability of the exfoliated modified graphene can be improved. The viscosity of the dispersion solution is more preferably 3.5 mPa·s or more, and even more preferably 4.0 mPa·s or more. In addition, by setting the viscosity of the dispersion solution to 25.0 mPa·s or less, the dispersion solution is easily introduced between the layers of the graphite composite, and shear force is easily applied to the graphite composite. The viscosity of the dispersion solution is preferably 20 mPa·s or less, more preferably 15 mPa·s or less, and even more preferably 10 mPa·s or less. Here, the viscosity of the dispersion solution is the viscosity measured at 20°C using an E-type viscometer.
[0054] (surface tension) The surface tension of the dispersion solution is preferably 10 mN / m to 60 mN / m. By setting the surface tension of the dispersion solution to 10 mN / m to 60 mN / m, the dispersion solution can be penetrated between the layers of the graphite composite while easily maintaining the interlayer distance of the modified graphene after delamination, and dispersibility can be improved. The surface tension of the dispersion solution is preferably 20 mN / m or more, more preferably 30 mN / m or more, more preferably 35 mN / m or more, and even more preferably 40 mN / m or more. In addition, the surface tension of the dispersion solution is preferably 55 mN / m or less, more preferably 50 mN / m or less, and even more preferably 45 mN / m or less. Here, the surface tension of the dispersion solution is the surface tension measured at 20°C using a capillary rise type surface tensiometer.
[0055] The dispersion solution preferably has a viscosity of 3 mPa·s to 25 mPa·s and a surface tension of 10 mN / m to 60 mN / m.
[0056] The dispersion solution and the graphite composite can be mixed so that the concentration of the graphite composite (i.e., the ratio of the graphite composite to the total of the graphite composite and the dispersion solution) is, for example, 0.1 mass % to 5 mass %, 1 mass % to 4.5 mass %, or 1.5 mass % to 4 mass %, etc.
[0057] Examples of the method of mixing while applying a shear force include ultrasonic treatment in which the mixture is stirred while irradiating ultrasonic waves, and pulverization treatment using a bead mill, jet mill, hammer mill, high-speed stirrer, etc. During mixing, it is necessary to control the temperature of the dispersion, and the temperature of the dispersion is usually controlled to about -5°C to 50°C. The temperature of the dispersion during mixing is preferably 0°C to 30°C.
[0058] The mixing time is appropriately selected depending on the mixing method, etc., but in the case of ultrasonic treatment, the treatment time can be, for example, about 5 minutes to 3 hours, or about 10 minutes to 2 hours.
[0059] The liquid obtained by stirring while applying a shear force can be used as it is as a graphene dispersion liquid. Alternatively, after stirring while applying a shear force, the liquid may be centrifuged to remove particles with a large particle size and improve dispersibility.
[0060] (Step of obtaining slurry) In the method for producing a slurry of the present invention, at least a positive electrode active material, a binder, a dilution solvent, and a graphene dispersion are mixed to obtain a slurry. The mixing method is not particularly limited, and a known method can be adopted. For example, a method of appropriately adjusting the solid content rate using a dilution solvent, kneading the positive electrode active material, the binder, and the graphene dispersion in a state where the solid content rate is high, and then reducing the solid content rate and further kneading can be mentioned.
[0061] When the conductive assistant contains modified graphene, carbon black and / or carbon nanotubes, a positive electrode active material, a binder, a dilution solvent, a graphene dispersion, and a powder or dispersion of carbon black and / or carbon nanotubes can be mixed to obtain a slurry. In this case, a method can be used in which the solid content is appropriately adjusted using a dilution solvent, the positive electrode active material, the binder, the graphene dispersion, and the powder or dispersion of carbon black and / or carbon nanotubes are kneaded in a state where the solid content is high, and then the solid content is reduced and further kneaded to adjust a slurry with a predetermined solid content.
[0062] <Positive electrode of lithium-ion battery> The slurry of the present invention can be used to manufacture a positive electrode of a lithium ion battery. For example, the slurry of the present invention is applied onto a current collector, dried, and then pressed to form a positive electrode active material layer on the current collector, thereby manufacturing a positive electrode of a lithium ion battery. The positive electrode active material layer is a layer formed by applying and drying the slurry of the present invention, and the diluting solvent in the slurry is removed by drying, so that the positive electrode of the manufactured lithium ion battery includes a current collector and a positive electrode active material layer formed on the current collector, and the positive electrode active material layer includes a positive electrode active material, a binder, and a conductive assistant containing modified graphene.
[0063] The shape and material of the current collector are not particularly limited, and known materials used for the positive electrode of lithium ion batteries can be appropriately selected and used. As the current collector, a metal foil having a thickness of about 10 μm to 100 μm is generally used, but it is not limited thereto, and a mesh-shaped current collector can also be used. As the material of the current collector, aluminum, copper, nickel, titanium, platinum, stainless steel, alloys thereof, etc. can be used.
[0064] <Lithium-ion battery> The positive electrode of the present invention can be combined with a negative electrode, a separator, and an electrolyte to form a lithium ion battery. The negative electrode, the separator, and the electrolyte can be selected from known materials. For example, graphite is used as the negative electrode. The separator can be a microporous membrane of polyethylene or polypropylene. The electrolyte can be a solution in which a lithium salt is used as the electrolyte and dissolved in an organic solvent. As the lithium salt, LiPF6, LiBF4, LiClO4, LiAsF6, LiSbF6, LiAlCl4, CF3SO3Li, C4F9SO3Li, CF3COOLi, (CF3CO)2NLi, (CF3SO2)2NLi, (C2F5SO2)NLi, etc. can be used. In addition, as the organic solvent, ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, etc. can be used. EXAMPLES
[0065] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the following examples unless the gist of the present invention is changed.
[0066] [Reference Example 1] Preparation of graphene dispersion (material) Graphite: flake graphite (Ito Graphite Industries Co., Ltd., CNP15) Lithium organic acid salt: Lithium citrate (tetrahydrate) (Kishida Chemical Co., Ltd.) Graphene dispersion improving polymer: Polyvinylidene fluoride (PVdF) (Kureha Corporation, homopolymer #7300, Mw: 1 million or more) Graphene dispersion solvent: N-methyl-2-pyrrolidone (NMP) (Kishida Chemical Co., Ltd.)
[0067] (Process (A)) At room temperature in air, 1 g of flake graphite and 2 g of lithium citrate were mixed for 30 minutes at a rotation speed of 500 rpm using a ball mill (Fritsch Japan Co., Ltd., planetary ball mill P-6S).
[0068] (Process (B)) 200 g of water was added to the mixture obtained in step (A), stirred at room temperature for 1 minute, washed with water, and then filtered. 200 g of water was added to the solid collected by filtration, stirred at room temperature for 1 minute, washed with water, and then filtered. The obtained solid was used in step (C) as a graphite composite of graphite and lithium citrate (composite (GR)).
[0069] (Process (C)) PVdF was dissolved in NMP to prepare a 0.2 wt% PVdF NMP solution as a dispersion solution. The composite (GR) and the dispersion solution were mixed so that the concentration of the composite (GR) was 3 mass%, and ultrasonic treatment was performed for 15 minutes while controlling the temperature of the dispersion solution to be 0 to 30°C, and a graphene dispersion solution was obtained by centrifugation (1,000G, 4 minutes).
[0070] [Reference Example 2] Preparation of graphene dispersion A graphene dispersion was obtained in the same manner as in Reference Example 1, except that in the step (C), the concentration of the composite (GR) was set to 3.85 mass %.
[0071] [Example 1] Production of slurry for forming positive electrode active material layer (positive electrode slurry) Positive electrode active material: LMO (LiMn2O4, Toshima Manufacturing Co., Ltd.) Graphene dispersion: Graphene dispersion prepared in Reference Example 1 Conductive additives (other carbon materials): Acetylene black (AB, Li-100, Denka Co., Ltd.) Binder: PVdF (Kureha Corporation, #9130 (NMP dissolved type)) Dilution solvent: NMP (Kishida Chemical Co., Ltd.)
[0072] The positive electrode active material, the graphene dispersion produced in Reference Example 1, acetylene black, PVdF, and NMP were kneaded so that 100 parts by mass of the positive electrode active material (LMO) was mixed with 2.85 parts by mass of acetylene black (AB), 0.15 parts by mass of modified graphene (GR), 5 parts by mass of PVdF, and the solid content (NV) was 60 wt%, to obtain a positive electrode slurry.
[0073] [Example 2] Manufacturing method of positive electrode The obtained slurry for the positive electrode was uniformly coated on an aluminum foil (made by UACJ, thickness 20 μm) using a doctor blade to a film thickness of 300 μm. After drying for 24 hours in a thermostatic chamber at 90° C., the coating was pressed to give an electrode coating weight of 22.7 g / cm. 2 The positive electrode was made of .
[0074] [Comparative Example 1] The positive electrode active material, acetylene black, PVdF (binder), and NMP used were the same as those in Example 1. Without using the graphene dispersion produced in Reference Example 1, the positive electrode active material, acetylene black, PVdF, and NMP were kneaded so that the amount of acetylene black was 3 parts by mass, the amount of PVdF was 5 parts by mass, and the solid content (NV) was 60 wt% relative to 100 parts by mass of the positive electrode active material, to obtain a positive electrode slurry. A positive electrode was produced in the same manner as in Example 2 using the obtained positive electrode slurry.
[0075] [Discharge rate evaluation] Positive electrode: Positive electrode produced in Example 2 or Comparative Example 1 Negative electrode: Li (thickness 0.2 mm, Honjo Metals Co., Ltd.) Electrolyte: LiPF61mol / L, EC: DMC (3:7v / v%), Kishida Chemical Co., Ltd. Separator: Polypropylene separator Using the above positive electrode, negative electrode, electrolyte, and separator, a sealed two-electrode cell (HS cell, Hosen) was assembled in a glove box with an argon gas atmosphere. EF-7100P (Electrofield) was used for charge / discharge measurements at 25°C. The charge conditions were CC-CV at 4.3V, and discharge was cut off at 3V with CC. The results are shown in Table 1.
[0076] [Table 1]
[0077] [Example 4] The positive electrode active material (LMO) was mixed with 96.5 parts by mass of the positive electrode active material, 1.5 parts by mass of the modified graphene (GR), 2 parts by mass of PVdF, and NMP so that the solid content (NV) was 60 wt %, to obtain a positive electrode slurry. The discharge capacity at 0.2 C was determined using the above method and was found to be 107 mAh / g.
[0078] [Reference example 3] At room temperature in air, flake graphite (Ito Graphite Industries Co., Ltd., CNP15) or flake graphite and an organic acid salt (lithium citrate (tetrahydrate) (Kishida Chemical Co., Ltd.), potassium citrate (monohydrate) (Kishida Chemical Co., Ltd.) or potassium carbonate (Kishida Chemical Co., Ltd.)) were added to a ball mill (Fritsch Japan Co., Ltd., planetary ball mill P-6S) and treated at a rotation speed of 500 rpm for 30 minutes. Next, 200 g of water was added, stirred at room temperature for 1 minute, washed with water, and then filtered. 200 g of water was added to the solid recovered by filtration, stirred at room temperature for 1 minute, washed with water, and then filtered. NMP was mixed so that the concentration of the graphite or graphite composite recovered by filtration was 1 g / L, and ultrasonic treatment was performed for 15 minutes while controlling the temperature of the dispersion to 10 ° C to 30 ° C, and a graphene dispersion was obtained by centrifugation (1,000 G, 4 minutes).
[0079] A predetermined amount of the obtained graphene dispersion was collected and completely dried at 100°C, and the mass (g) of the residue was measured. The mass (g) of the residue was divided by the amount (L) of the collected dispersion to determine the concentration (g / L) of modified graphene in the graphene dispersion. Table 2 shows the graphene concentration in the obtained graphene dispersion.
[0080] [Table 2]
[0081] [Reference example 4] A graphene dispersion was obtained in the same manner as in Reference Example 1, except that the mixing by the ball mill in step (A) was performed for 60 minutes, the ultrasonic treatment in step (C) was performed for 60 minutes, and the concentrations of the dispersion solution and the composite (GR) were as shown in Table 3.
[0082] The viscosity of a 0.2 wt% PVdF NMP solution was measured using an E-type viscometer (Toki Sangyo Co., Ltd., model number: TV-100H, standard cone rotor) at 20°C and a shear rate of 100 s. -1 The viscosity was measured at 20°C using a capillary rise type surface tensiometer (Hyomen Sokki Seisakusho, DG-1) and was found to be 4.0 mPa s. The surface tension of the prepared dispersion was measured at 20°C using a capillary rise type surface tensiometer (Hyomen Sokki Seisakusho, DG-1) and was found to be 42.5 mN / m. Similarly, the viscosity and surface tension of NMP were measured and found to be 1.9 mPa s and 39 mN / m.
[0083] In the same manner as in Reference Example 3, a predetermined amount of a portion of the graphene dispersion was collected, and the concentration of modified graphene in the graphene dispersion (converted to g / L) was determined. From the obtained value, the amount (g) of modified graphene in the entire graphene dispersion was calculated, and the amount (g) of modified graphene in the entire graphene dispersion was divided by the composite (GR) used in step (C) to calculate the recovery rate (= amount (g) of modified graphene in graphene dispersion / amount (g) of composite (GR) used in step (C)×100(%)). In addition, for those to which PVdF was added, the mass (g) of PVdF in the collected graphene dispersion was calculated from the concentration of PVdF, and the concentration (g / L) of modified graphene in the graphene dispersion was calculated from "(mass (g) of residue-mass (g) of PVdF) / collected amount (L)". Table 3 shows the results.
[0084] [Table 3]
Claims
1. A positive electrode active material, a binder, a dilution solvent, and a conductive assistant including modified graphene, The slurry for forming a positive electrode active material layer of a lithium ion battery, wherein the modified graphene contains lithium ions and graphene having an anionic site to which an organic acid is bonded.
2. the slurry contains the positive electrode active material, the binder, the dilution solvent, and a graphene dispersion, 2. The slurry for forming a positive electrode active material layer of a lithium ion battery according to claim 1, wherein the graphene dispersion is a dispersion containing the modified graphene, a graphene-dispersibility-improving polymer that constitutes at least a part of the binder, and a graphene dispersion solvent that constitutes at least a part of the dilution solvent.
3. The binder is a fluorine-based polymer, 2. The slurry for forming a positive electrode active material layer of a lithium ion battery according to claim 1, wherein the dilution solvent is N-methyl-2-pyrrolidone.
4. The slurry for forming a positive electrode active material layer of a lithium ion battery according to claim 1 , wherein the organic acid is citric acid.
5. 3. The slurry for forming a positive electrode active material layer of a lithium ion battery according to claim 2, wherein the graphene dispersion improving polymer has a weight average molecular weight (Mw) of 600,000 or more.
6. The slurry for forming a positive electrode active material layer of a lithium ion battery according to claim 1 , wherein the conductive assistant comprises the modified graphene, and carbon black and / or carbon nanotubes.
7. The method includes at least a step of mixing the positive electrode active material, the binder, the dilution solvent, and a graphene dispersion to obtain a slurry, 6. The method for producing a slurry for forming a positive electrode active material layer of a lithium ion battery according to any one of claims 1 to 5, wherein the graphene dispersion is a dispersion in which the modified graphene is dispersed in a graphene dispersion solvent that constitutes at least a part of the dilution solvent.
8. the graphene dispersion includes the modified graphene, a graphene-dispersibility improving polymer that constitutes at least a part of the binder, and the graphene dispersion solvent, Prior to the step of obtaining the slurry, a step (A) of mixing and pulverizing the organic acid lithium salt, which is a salt of an organic acid and lithium ions, and graphite in a dry or paste form; a step (B) of washing the mixture obtained in the step (A) with water to obtain a graphite composite of graphite and an organic acid lithium salt; a step (C) of mixing the graphite composite with a dispersion solution in which the graphene dispersibility improving polymer is dissolved in the graphene dispersion solvent while applying a shear force, thereby exfoliating the graphite composite in the dispersion solution to obtain the graphene dispersion; having 8. The method for producing a slurry for forming a positive electrode active material layer of a lithium ion battery according to claim 7, wherein the viscosity of the dispersion solution in the step (C) is 3.0 mPa·s to 25.0 mPa·s, and the surface tension of the dispersion solution is 10 mN / m to 60 mN / m.
9. the slurry contains the modified graphene and carbon black and / or carbon nanotubes as the conductive assistant; 8. The method for producing a slurry for forming a positive electrode active material layer of a lithium ion battery according to claim 7, wherein in the step of obtaining the slurry, the positive electrode active material, the binder, the dilution solvent, the graphene dispersion, and a powder or dispersion of the carbon black and / or the carbon nanotubes are mixed to obtain a slurry.
10. A positive electrode active material layer is formed on a current collector. the positive electrode active material layer includes a positive electrode active material, a binder, and a conductive assistant including modified graphene, The positive electrode of a lithium ion battery, wherein the modified graphene comprises graphene having anionic sites to which an organic acid is bound and lithium ions.
11. A lithium ion battery comprising the positive electrode according to claim 10.
Citation Information
Patent Citations
Inorganic particle composite, production method thereof, and inorganic particle composite dispersion
JP2019147713A
Positive electrode for lithium ion secondary battery
JP2022167301A
Carbon nanotube dispersion and use thereof
WO2022075387A1